Africa 2.0 : inside a continent's communications revolution - Southwood, Russell (Manchester University Press, 2022)
Africa wired up provides an important history of how two technologies - mobile calling and internet - were made available to millions of Sub-Saharan Africans and the impact they have had on their lives. The book deals with the political challenges of liberalization and privatization that needed to be in place to get these technologies built.